PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA INDIVIDU DENGAN PENERAPAN SISTEM INFORMASI AKUNTANSI SEBAGAI VARIABEL INTERVENING - Hilendri, Bq. Anggun; Nurabiah, Nurabiah; FR, Aditya Fajar (Jurnal Aplikasi Akuntansi, 2018)
The objective of this study is to examine the influence of organizational culture on individual performance with accounting information system application as intervening variable. This study uses primary data obtained through the distribution of questionnaires to respondents, who are employees working on the clothing distribution store or outlet (Distro) in the Mataram city. The sample of this study consisted of 102 respondents, which is determined based on purposive sampling method. The results of this study indicate that organizational culture has a significant and positive influence on individual performance. Organizational culture also has a significant and positive influence on accounting information system application. However, the application of accounting information system as intervening variable has no influence on individual performance. Likewise the study also found that application of accounting information systems has no indirect influence of organizational culture on the performance of individuals. Businessmen who apply accounting information system in the form of application of accounting software especially on the distrocould use the result of this research, as well as employees as the user of the accounting software in order to understand in advance the steps to apply it thoroughly.